PENGARUH PENERAPAN METODE JARIMATIKA TERHADAP KEMAMPUAN BERHITUNG BILANGAN BULAT POSITIF PADA SISWA KELAS IV A MIN MALAWELE - Muhammad Akram G (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2020)
This research is motivated by the students' low numeracy skills. Based on the results of observations by researchers in class IVA during the implementation of PPL in the 2017/2018 academic year, from 21 students, there were 14 students who were not proficient in arithmetic (66%) and those who were proficient but still needed guidance, there were 7 students (34%). In this case, the researcher tried an experimental study in mathematics learning, especially positive integer material using the Jarimatika method. Based on the descriptive statistical calculation of the average pretest and posttest mean with a total of 21 students, the pretest average obtained a minimum value of 23.75, a maximum value of 96.25, an average value of 66.07, and a standard deviation of 18.688, while the average postest obtained a minimum value of 61.25, a maximum value of 97.50, an average value of 81.72 and a standard deviation value of 10.922. This study was declared successful by looking at the difference in the average pretest and postest results from 66.07 to 81.72. This shows that there is an effect of the Jarimatika method on the counting ability of positive integers in class IVA MIN Malawele, Sorong Regency